Hubungan antara Kualitas Kehidupan Kerja dengan Komitmen Organisasi pada Karyawan Perusahaan Genteng Mutiara - Angelia, Nuriza (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2013)
Abstract The purpose of this research is to find out the correlation between quality of worklife with organizational commitment. Hyphothesis proposed is that there is a positive correlation between quality of worklife with organizational commitment. The higher the quality of worklife then the higher the organizational commitment. The lower the quality of worklife then the lower the organizational commitment. Respondens in this study were employee of Genteng Mutiara manufactured in Sleman. The sample of 52 respondens participated in this research. This research use a scale which is contructed by the researcher, the scale of quality of worklife is used in this research based on the explanation from aspects stated by Walton (Robbins, 2002) and the scale of organizational commitment based on the aspects stated by Steers and Porter (1996). The tatistical technique used with computer program Statistical Product and Service Sollution (SPSS) 18.0 for windows to test the hypothesis is product moment correlation test of Pearson. Results show the correlation coefficient with sig: 0,000 for quality of worklife and sig: 0,000 for organizational commitment (P < 0,01). This research shows that there is significant positive correlation between quality of worklife with organizational commitment, hypothesis accepted. Key Words : organizational commitment, quality of worklife